'Micro-Gold' Miniature Dwarf Tomato - John W. Scott; Brent K. Harbaugh (EDIS)
'Micro-Gold' is a miniature dwarf tomato (Lycopersicon esculentum Mill.) with gold-colored fruit. It is a comparison to 'Micro-Tom' (Scott and Harbaugh, 1989), which has been the smallest tomato cultivar released to date. Like 'Micro-Tom', 'Micro-Gold' is being released as a tomato that can be grown singly in small pots (13 cm in diameter; 1-liter volume), as three plants in hanging pots (15 cm in diameter, 1.8-liter volume), or more plants in larger hanging pots. It is also ideal for window boxes or garden borders because the plant canopy diameter is only 19 cm (spring) to 26 cm (fall) (Table 1). 'Micro-Gold' combines ornamental aspects of a well-proportioned, diminutive, tomato plant with a mild-tasting fruit that can be eaten. The small plant size makes it ideal for commercial growing, shipping, and retail selling. This is document HS987, a publication of the Horticultural Sciences Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication date: June 2004.